THE CONTRIBUTION OF SPEAKING PRACTICE WITH THE NATIVE SPEAKER TO STUDENTS’ SPEAKING ABILITY IN SMPN 1 PAMEKASAN - Devie Reztia Anjarani; Muhammad Darrin Zuhri; Jamaluddin (Universitas PGRI Palembang, 2025)
This study examines the impact of speaking practice with native speakers on the English-speaking skills of students at SMPN 1 Pamekasan. It investigates how direct interactions with native speakers affect linguistic fluency, pronunciation, and confidence in speaking. Using a mixed-method approach, the research collected data through observations, interviews, and performance evaluations of eighth-grade students actively involved in speaking activities with native speakers. The findings reveal that regular interaction with native speakers significantly enhances students’ speaking abilities, particularly in pronunciation accuracy and conversational competence. Furthermore, the study emphasizes the role of authentic language practice in boosting student engagement and motivation in learning English. These results underscore the potential benefits of integrating native speaker interactions into English language teaching programs to improve students' speaking proficiency.